STUDI ANALISIS KOMPETENSI PEDAGOGIK GURU PENDIDIKAN KEWARGANEGARAAN DALAM PENGUASAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA SMP NEGERI DI KECAMATAN SELOGIRI - ., Yunitasari; Muchtarom, Moh.; Yuliandari, Erna (PKn Progresif, 2016)
This research aimed to find out (1) the Civic Education teacher?s mastery of Information Technology and Communication (ICT)-based learning media in public junior high schools in Selogiri Sub District; (2) the Civic Education teacher?s awareness of using ICT-based learning media; (3) the attempt taken by headmaster to use the Civic Education teacher?s mastery in using ICT-based learning media; and (4) Civic Education teacher?s pedagogic competency viewed from the mastery of ICT-based learning media in Public Junior High School in Selogiri Sub District.This study employed a qualitative interactive method and qualitative descriptive approach with case study. The data source included informant, place, activity, document with purposive sampling. Techniques of collecting data were interview, observation, and documentation study. To validate the data, data and method triangulations were used. Considering the result of research were: (1) Civic Education teacher?s mastery of ICT-based learning media in public junior high schools in Selogiri Sub District was still low in which Civic Education teacher?s knowledge and ability of using computer, LCD, internet, various information and media, and of dealing with barrier or constraint in using ICT-based learning media were still limited; (2) the Civic Education teacher?s awareness of using ICT-based learning media was still low because the attempt of learning anything related to ICT-based learning media, there had been no personal willingness in using ICT-based learning media, and there had been no willingness and attempt of selecting the ICT-based learning media relevant to Civic Education. (3) The attempts taken by the headmaster to improve the Civic Education teacher?s mastery of ICT-based learning media were moderately and fairly good including providing infrastructure, holding training of ICT, giving moral support /advice/instruction/direction to Civic Education teacher in order to improve the mastery and the utilization of ICT. (4) Civic Education teacher?s pedagogic competency in Public Junior High Schools in Selogiri Sub District was still low viewed from the mastery of ICT-based learning media.